Translation and Adaptation of Planned Happenstance Career Inventory in Urdu Language - Numera Younus; Nadia Ayub (Journal of Education and Educational Development, 2023)
The present study was aimed to achieve two objectives: (a) translate and adapt the English version of Planned Happenstance Career Inventory (PHCI) in Urdu language, and (b) to establish its psychometric properties with respect to Pakistani culture. The study was divided into two phases. Phase I consisted of forward and backward translation of the scale and its initial statistical analysis, whereas Phase II was focused on establishing the psychometric properties. Results of the Phase I yielded reliable. Phase II analysis yielded correlation (r = .732, p < .01), on a sample of (n=87), which suggests strong Test-Retest reliability whereas discriminant validity was proved with insignificant relationship of Counterproductive Work Behaviour Checklist and PHCI-Urdu version (r = .018, p > .05), and significant correlation with Urdu Rosenberg Self-Esteem Scale (r = .358, p < .01) proved the convergent validity of the two scales. This study concludes that PHCI- Urdu would be an effective tool for individual career counselling as well as trainings related to career counselling to prepare students for uncertain circumstances from public and private educational sectors.
Keywords: career counseling; planned happenstance; psychometrics; reliability; validity